Enhanced photoelectrocatalytic performance of WO3|ZnO heterojunction film for moxifloxacin oxidation - brandao, Aline Estefany; P Sousa, Renato; F.S. Filho, Antônio; G R da Costa, Antonio; J P S Neto, Antonio; E da Luz Júnior, Geraldo; R P Garcia, Ramón; O M Gusmão, Gustavo (XIV Encontro de Catálise do Norte, Nordeste e Centro-Oeste, 2024)
Environmental problems caused by wastewater contamination by antibiotic residues have gained great importance in recent years. Advanced oxidation processes have been a viable and sustainable alternative to mitigate these effects. Based on this, the present study successfully fabricated FTO|WO3|ZnO heterojunction films for the enhanced oxidation of the drug moxifloxacin in water. SEM images showed that the FTO|WO3|ZnO heterojunction films presented high porosity and a thickness of 8.314 μm. In addition, the film exhibited excellent photoelectrochemical performance, achieving a photocurrent density and recombination time higher than that observed for the pure WO3 film. Finally, the FTO|WO3|ZnO film exhibited good photocatalytic performance, with approximately 48.00% degradation of MOX, confirming that the combination of materials favored a higher photocatalytic efficiency.